(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employee engagement refers to the extent of an employee’s enthusiasm and loyalty toward their job, company, and objectives. Engaged employees exhibit a heightened commitment to their employer, leading to superior work quality and indicative job contentment.